Osmoregulatory function of betaine in alleviating heat stress in poultry. Issue 6 (20th September 2018) - Ratriyanto, Adi; Mosenthin, Rainer
Abstract: This review focuses on the osmoregulatory function of betaine and its effect in terms of alleviating heat stress in poultry. Poultry appear to be particularly sensitive to temperature‐associated environmental challenges, especially heat stress. High ambient temperatures are deleterious to productive performance in poultry, including broilers, laying hens, quails and turkeys, resulting in considerable economic losses. Heat stress impairs overall poultry production by decreasing feed intake and negatively affecting intestinal development, leading to reduced nutrient digestibility. Apart from inducing a high mortality rate, heat stress is known to depress growth rate and reduce meat yield in broilers. In layers, lower feed intake impairs ovarian function, leading to decreased feed efficiency, egg production and egg quality. In addition, reduced immune functions, such as thyroid activity and antibody production, are evident in poultry exposed to heat stress. Heat stress increases the production of oxidants, causing oxidative stress and lipid peroxidation of cell membranes. Poultry respond physiologically and behaviourally when encountering the negative effects of heat stress, attempting to return the body to homeostasis. This requires energy at the expense of weight gain or egg production. Due to its zwitterionic structure, betaine has osmoprotective properties that aid in protecting intestinal cell proteins and enzymes from environmental stress, including high ambient temperature, thereby counteracting performance losses. Betaine also exerts an osmoregulatory role in cells, regulating water balance, and this results in more stable tissue metabolism. Inclusion of betaine in the diet may be beneficial for alleviating physical reactions to heat stress, as indicated by increases in nutrient digestibility. In broilers, betaine supplementation increases weight gain and breast muscle yield, while improving feed conversion. In layers, betaine supplementation improves egg production, egg quality traits and immune indices. In conclusion, due to its osmoregulatory functions, betaine plays an important role in alleviating heat stress in poultry.